Kannada navodaya kavya: mangaluru kendra. - GIRADDI GOVINDARAJA, Ed. 9 (Bengaluru. Karnataka Sahitya Akademi., 2001)
Muddana Hattiyangadi Narayanaraya Govinda Pai Panjemagesharaya Kadengodlu Shankarabhatta Sediyapu Krashna Bhatta Kolambe Puttanna Gauda Pejavara Sadashivaraya Kayyara Kinanna Rai Yarmunja Ramachandra
Keywords: 9; 9; 9; 9; 9; 9; 9; 9; 9; 9